Understanding the influence of marine nutrients on insectivorous and herbivorous reptiles in the Gulf of California islands - Ilse K. Barraza-Soltero; MCarmen Blázquez; Salvador Hernández-Vázquez; Antonio Delgado-Huertas; Víctor M. Muro-Torres (PLoS ONE, 2025)
Marine subsidies in the extremely arid islands of the northern Gulf of California have been shown to be important enhancing primary productivity and fueling the terrestrial food webs. This effect has been proved in plants, insects, lizards and rodents. The aims of our study were first to determine whether insectivorous lizards from a wide array of islands, including some in the central and southern part of the Gulf, are consuming marine derived products, and secondly to assess its impact on herbivore lizards as well. We hypothesized that the availability and use of marine nutrients for lizards would vary depending on island aridity, island size, and the presence of seabird colonies nearby. To test the hypothesis, we analyzed the isotopic niches of 13 populations of insectivorous lizards (genus Uta) and 9 populations of herbivore iguanas (genera Dipsosarus, Ctenosaura, and Sauromalus) across 16 islands spanning 5 latitude degrees and 350 nautical miles. Our results showed that the proximity of seabird colonies play a key role in reinforcing the presence of marine origin nutrients in both insectivorous and herbivore populations. The ubiquity of seabird colonies on the northern islands combined with higher aridity in the northern part of the Gulf, creates a northward gradient in the importance of marine subsidies for both insectivorous and herbivore lizards, across the Gulf islands. δ13C variation in insectivorous lizards’ tissues was significantly correlated with island aridity/latitude, while the presence of significant seabird colonies nearby was significantly correlated with δ15N variation. The results were less clear in the herbivore group of species. Insectivorous and herbivorous share a large portion (70%) of their isotopic space. The incorporation of the highly enriched 15N to both type of lizards is happening for the two possible ways, the presence of guano, that may be driving plant fertilization, and the direct consumption of insects associated to the birds (or birds’ products, as eggs or corpses); but we could not differentiate between them. The size of the islands was not relevant in our results, possibly due to our sampling design. Additional isotopic analysis of plants and arthropods and in a gradient coast-inland could provide a more comprehensive view of the nutrient flow within these island ecosystems and the effect of the island size.